Hubungan Pengetahuan dan Dukungan Suami terhadap Kepatuhan Ibu Hamil dalam Melakukan Kunjungan Pemeriksaan Kehamilan ( ANC ) - Norlia lia; Yuniarti Yuniarti; Rubiati Hipni; Rita Kirana (JURNAL KEBIDANAN BESTARI, 2025)
Introduction: Pregnancy examination is an important part of the birthing process and will have a positive impact on the pregnant mother and the fetus she is carrying. Pregnant women who know the benefits and importance of prenatal check-ups will be more compliant in carrying out ANC visits compared to pregnant mothers who don't know about it. Objective: This study aims to analyze the relationship between knowledge and support from husbands on pregnant women's compliance in carrying out pre-natal check-up at the Tirta Jaya Community Health Center, Tanah Laut Regency. Method: ANC visit data was obtained from the KIA book,cohort register,while husband's knowledge and support variables were obtained through a questionnaire distributed to selected respondents. To determine the relationship between these two variables, the chi square test was used. Results: The results of the research conducted showed that a relationship was found between knowledge and compliance (p value of 0.029 ± 0.05). Pearson's Chi square test shows a figure of 5.776 or 57.76% for the knowledge variable and a p-value of 0.029 ± 0.05 for the husband's support variable. Conclusion: The results of the study show that knowledge and support have a strong relationship with the intensity of pregnancy check-up visits for pregnant women, as evidenced by the existence of a significant relationship between variables, namely husband's knowledge and support for compliance. Keywords: husband's support, Pregnancy examination, Knowledge